Monitoring maternal and newborn health outcomes globally: a brief history of key events and initiatives - Moller, Ann-Beth (Trop Med Int Health, 2017)
OBJECTIVE: Over time, we have seen a major evolution of measurement initiatives, indicators and methods, such that today a wide range of maternal and perinatal indicators are monitored and new indicators are under development. Monitoring global progress in maternal and newborn health outcomes and development has been dominated in recent decades by efforts to set, measure and achieve global goals and targets: the Millennium Development Goals followed by the Sustainable Development Goals. This paper aims to review, reflect and learn on accelerated progress towards global goals and events, including universal health coverage, and better tracking of maternal and newborn health outcomes. METHODS: We searched for literature of key events and global initiatives over recent decades related to maternal and newborn health. The searches were conducted using PubMed/MEDLINE and the World Health Organization Global Index Medicus. RESULTS: This paper describes global key events and initiatives over recent decades showing how maternal and neonatal mortality and morbidity, and stillbirths, have been viewed, when they have achieved higher priority on the global agenda, and how they have been measured, monitored and reported. Despite substantial improvements, the enormous maternal and newborn health disparities that persist within and between countries indicate the urgent need to renew the focus on reducing inequities. CONCLUSION: The review has featured the long story of the progress in monitoring improving maternal and newborn health outcomes, but has also underlined current gaps and significant inequities. The many global initiatives described in this paper have highlighted the magnitude of the problems and have built the political momentum over the years for effectively addressing maternal and newborn health and well-being, with particular focus on improved measurement and monitoring.